Prevalence of common mental disorders among medical students during the Covid-19 pandemic - Cardoso,Ane Caroline Cavalcante (2022)
Abstract: Introduction: Common mental disorders (CMD) have been frequently identified among university students in the health area, especially in Medicine. It is believed that characteristics inherent to the course have a potential influence on the student’s mental health. When adding the pandemic context, with its inherent social restrictions, the psychological determinants related to the unknown pathology and the fear of the rapid spread of the new coronavirus, there is the possibility of increasing the risk factors for psychological distress in this population. Objective: To estimate the prevalence of CMD among medical students during the COVID-19 pandemic, analyzing its main determinants in the academic, social and economic spheres. Method: Cross-sectional study, carried out with 388 medical students in Salvador/BA., Data on sociodemographic and academic aspects, life habits, comorbidities and symptoms of non-psychotic disorders were collected using the Google Forms platform, measured by the Self-Reporting Questionnaire (SRQ-20). Results: The prevalence of CMD was 39.7% among medical students, with 47.4% in the basic cycle, 40.3% in the clinical cycle and 12.3% in the internship period. Among the factors associated with the emergence of CMD are sedentary lifestyle, smoking, use of substances that enhance academic performance, dissatisfaction with one’s academic performance, poor sleep quality, lack of appetite, frequent headaches, poor digestion, suicidal ideation and sadness. There was a higher rate of non-psychotic mental disorders among women, with no difference regarding the academic cycle and the administrative type of the educational institution. Conclusion: During the COVID-19 pandemic, a significant prevalence of CMD was demonstrated among female, white, single medical students who live with family members and do not have their own income. Although studies suggest an increase in the prevalence among university students at the present time, the data from the present study remain in agreement with the literature data prior to the pandemic, showing that the medical course itself is the main risk factor for higher rates of CMD in this population. However, further studies on the long-term impact of the pandemic on the mental health of university students are still necessary.